Ground state structural, lattice dynamic, thermodynamic and optical properties of the Ba₂CaMoO₆ ordered perovskite - Deluque Toro, Críspulo Enrique (2023)
Ab-initio calculations based on density functional theory have been performed to establish the ground state properties for the double perovskite type material Ba₂CaMoO₆. The calculations were carried out through the Projector Augmented Wave Method and the exchange and correlation was described using the Perdew-Burke- Ernzerhof parameterization of the Generalized Gradient Approximation. The study included structural analysis of the material, as well as thermodynamic, cell dynamics and optical properties at its transition between the tetragonal I4/m and cubic Fm 3 m phases. The results on the structural stability reveal that the phase with space group of I4/m is more stable. Likewise, the structural phase transition was obtained for a pressure of 0.067 GPa. On the other hand, the analysis of the electronic properties shows that the material presents a semiconducting behaviour, with a direct band gap of 2.40 eV and 2.26 eV for the tetragonal and cubic structures, respectively. In addition to agreeing with the experimental values reported in the literature, the results suggest possibilities for the application of this material in photodetectors, light emitters and devices for power electronics.